Identification and Functional Analysis of Four RNA Silencing Suppressors in Begomovirus Croton Yellow Vein Mosaic Virus - Zhai, Ying; Roy, Anirban; Peng, Hao; Mullendore, Daniel L.; Kaur, Gurpreet; Mandal, Bikash; Mukherjee, Sunil Kumar; Pappu, Hanu R. (Frontiers in Plant Science, 2022)
Croton yellow vein mosaic virus (CYVMV), a species in the genus Begomovirus, is a prolific monopartite begomovirus in the Indian sub-continent. CYVMV infects multiple crop plants to cause leaf curl disease. Plants have developed host RNA silencing mechanisms to defend the threat of viruses including CYVMV. We characterized four RNA silencing suppressors, V2, C2 and C4 encoded by CYVMV and βC1 encoded by the cognate betasatellite, croton yellow vein betasatellite (CroYVMB). Their silencing suppressor functions were verified by the ability of restoring GUS activity suppressed by RNA silencing. We show here for the first time that V2 was capable of self-interacting as well as interacting with the V1 protein and could be trans-localized to the plasmodesmata in the presence of CYVMV. Knockout of either V2 or V1 impaired CYVMV intercellular mobility, indicating their novel coordinated roles in cell-to-cell movement of the virus. As pathogenicity determinants, each of V2, C2 and C4 could induce typical leaf curl symptoms in Nicotiana benthamiana plants even under transient expression. Interestingly, the transcripts and proteins of all four suppressors could be detected in the systemically infected leaves with no correlation to symptom induction. Overall, our work identifies four silencing suppressors encoded by CYVMV and its cognate betasatellite, and reveals their subcellular localizations, interaction behavior and roles in symptom induction and intercellular virus movement.